An Analysis of Translating Procedures In Iphone Start Up Guide Book - Irma Manda Negara; Ida Nurbaiti (STBA Pontianak, 2017)
This research aims to identify translation prodecures and methods used by the translator in translating iphone 5 start up guide book from English as source language into Indonesia as target language. Qualitative descriptive was employed to analyse the data by referring the theories proposed by Newmark (1991:17). The result of data analysis shows that there are six translation procedures found in the text: transposition (126 items or 21%), modulation (91 items or 15%), borrowing (164 items or 27%), calque (60 items or 10%), equivalence (87 items or 15%) and reduction (72 items or 12%). whereas for the methods that used by the translator are 233 items or 39% using literal, faithful (146 items or 24%), adaption (144 items or 24%), communicative (77 items or 13%).